2011
DOI: 10.1039/c1cp20238c
|View full text |Cite
|
Sign up to set email alerts
|

In situ infrared monitoring of the solid/liquid catalyst interface during the three-phase hydrogenation of nitrobenzene over nanosized Au on TiO2

Abstract: The three-phase hydrogenation of nitrobenzene catalysed by nanosized gold over titania was investigated in a slurry. Simultaneous in situ ATR-FTIR monitoring of the liquid phase and at the solid/liquid catalyst interface identified the species adsorbed on the catalyst and those in the liquid phase during the reaction. Nitrosobenzene was not detected analytically while the spectroscopic measurements strongly indicated phenylhydroxylamine as an intermediate reacting before desorbing from the catalyst surface. Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
84
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(86 citation statements)
references
References 43 publications
2
84
0
Order By: Relevance
“…NC: nitrocompound, NSC: nitrosocompound, AHA: aromatic hydroxylamine, AN: aniline, AOC: azoxycompound, AC: azocompound, HAC: hydrazocompound. Adapted from Richner et al [15] In the present work we show that it is possible to produce azocompounds with more than 98% yield from nitrobenzene in a single pass with a catalyst able to preferentially direct the process towards the coupling of nitrosobenzene intermediate (condensation route a.1 in Scheme 2). In this way the azoxycompound is formed that selectively evolves to the desired azocompound.…”
Section: Methodsmentioning
confidence: 59%
See 1 more Smart Citation
“…NC: nitrocompound, NSC: nitrosocompound, AHA: aromatic hydroxylamine, AN: aniline, AOC: azoxycompound, AC: azocompound, HAC: hydrazocompound. Adapted from Richner et al [15] In the present work we show that it is possible to produce azocompounds with more than 98% yield from nitrobenzene in a single pass with a catalyst able to preferentially direct the process towards the coupling of nitrosobenzene intermediate (condensation route a.1 in Scheme 2). In this way the azoxycompound is formed that selectively evolves to the desired azocompound.…”
Section: Methodsmentioning
confidence: 59%
“…In opposite, nitrosobenzene adsorbs differently on both catalyst ( Figure 7). On Au/TiO 2 nitrosobenzene is found to be coordinated to a surface metal site by a -N bonding (characterized by the 1485 cm -1 N=O stretching IR band [15,17] ), while on Au/CeO 2 , in addition to an interaction of the N=O group by -N (IR band at 1485), a -O bonding (IR bands at 1520-1508 cm -1 ) and an interaction of the N=O group with surface oxygen ions (IR band at 1540 cm -1 ) is observed [17] . The higher basicity of the oxygen ions in the ceria nanoparticles explains the former stabilization mode of nitrosobenzene on the catalysts surface.…”
Section: Ir Spectroscopic Studiesmentioning
confidence: 99%
“…Because of earlier results, which showed that a high nitrosobenzene concentration poisoned the reaction, [6] we decreased the concentration of nitrosobenzene in this experiment from 0.8 to 0.4 mmol, which did not result in catalyst poisoning. All other reaction conditions were the same as in Figure 1.…”
mentioning
confidence: 85%
“…The direct route dominates over Au/TiO 2 , [17b, 18] and accumulation of phenylhydroxylamine on the surface of the catalyst has been observed. [6] We found that hydrogenation was sufficiently fast over Au/TiO 2 to prevent condensation of phenylhydroxylamine with nitrosobenzene, which was formed either from nitrobenzene or by phenylhydroxylamine decomposition, but slower than over Au/CeO 2 . Phenylhydroxylamine has been found as an intermediate on the surface of the catalyst during the liquid-phase hydrogenation of nitrobenzene by using liquid-phase attenuated-total-reflectance (ATR) IR measurements.…”
mentioning
confidence: 98%
“…A more detailed scheme on NO 2 group hydrogenation can be found elsewhere. 39 Under the reaction conditions used, the IL-supported Pt NP catalyst retained its preferential activity for the CC double bond. The selectivity for ENB of this catalyst was only moderate and continuously decreased with conversion (Figure 1), reaching a value of 61% at around 90% conversion.…”
Section: ■ Resultsmentioning
confidence: 95%